Requirements for an Allocation Center for the Flight Centric Air Traffic Control Concept - Tobias Finck; Bernd Korn (Engineering Proceedings)
Nowadays, the allocation of aircraft to controllers is easily conducted. All aircraft entering a specific sector are automatically allocated to the responsible controller team. With increasing air traffic, it has become evident that this longstanding sector-based system needs to be replaced by innovative concepts such as Flight Centric ATC to meet the rapidly growing capacity demands. Flight Centric ATC requires novel systems for the allocation of aircraft to controllers, known as the Allocation Center. This Allocation Center has only been examined rudimentarily in current studies on Flight Centric ATC. The necessary requirements have not yet been taken into consideration in detail. This paper therefore both analyzes the general structure of an Allocation Center based on five high-level needs and also defines eleven operational requirements for such a center.